Meera‘s Contribution in the Social and Cultural Field: Meera: A Revolutionary Figure in Medieval Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Discussing the freedom and equality of women in the medieval era was a revolutionary advance. Starting here of view, she is a symbol of public awareness. In communalism, he lit a light of public awareness by putting forth an excellent attempt to liberate the devotional soul from the ceremony and bad faith. He had made Krishna Bhakti the inspiration of public awareness. Meera's life esteems have contributed fundamentally to the advancement of nationality. Crafted by Mira show a striking cultural cognizance against a wide range of traditionalist convictions and class contrasts. The foundation of government assistance and salvation programs of untouchables to be held in India was laid by Meera and different holy people. In Meeran's personality and appreciation, we discover the fire of class absolutism presumed against feudal culture, which accelerated the programs of social change in the coming occasions. The discussion of social concordance appears to have acquired some life in our country around the eighteenth century. However, Meera's endeavors can be seen growing in the sixteenth century. In medieval holy person literature, there is a qualification among high and low about casteism. The feeling of solidarity in the nation is firmly upheld by eliminating the supposition asking caste and caste, kindly send it to Hari, so Hari had a place with it. Have accepted family, and so on.